Beyond Suppression: Peripheral T Cell Responses to Vaccination in Inflammatory Bowel Disease Patients Undergoing Anti-Tumor-Necrosis-Factor Therapy - Martin Qui; Ennaliza Salazar (Vaccines)
Alimentary tract inflammation in inflammatory bowel disease (IBD) is treated by systemically administered drugs that alter fundamental host immune responses. Biologics that target tumor necrosis factor (TNF) are first-line biologics in IBD, used widely for their effectiveness, steroid-sparing quality, and lower cost. While they enable a significant proportion of patients to achieve clinical remission, they carry an increased risk of infection and poor serological responses to vaccination. Conversely, our understanding of adaptive T cell responses in anti-TNF-treated IBD patients remains limited. The introduction of COVID-19 vaccines has prompted research that both challenges and refines our view on immunomodulatory therapy and its potential implications for immunity and protection. Here, we review these emergent findings, evaluate how they shape our understanding of vaccine-induced T cell responses in the context of anti-TNF therapy in IBD, and provide a perspective highlighting the need for a holistic evaluation of both cellular and humoral immunity in this population.